The Digital Nexus of Creativity: Mediating Roles of Self-Competence and Self-Efficacy in AI Use and Digital Literacy - Dzingai Katsamba (Journal of Advanced Research in Social Sciences and Humanities, 2025)
Aim: Artificial intelligence promoting problem-solving abilities and creative learning that can be valuable for student’s creativity. The present study examines that use of AI, digital literacy with student’s creativity and promotes support system of creative skills of students through AI tools among Africa based university students. Also, self-competence and self-efficacy act as mediation and academic support as moderator among use of AI, digital literacy and students creativity. Methodology: A longitudinal research design used for data collection in three waves in last six months and total sample size was 320 students of African universities. However, mediation moderation analysis by SmartPLS 3.0 with measurement and structural model. Findings: The significant mediating relationship of self-competence and self-efficacy among use of AI, digital literacy and students creativity. Furthermore, moderating impact of academic support on AI usage and digital literacy with self-competence, and self-efficacy was also confirmed. Implications/Novel Contribution: These results imply that incorporating artificial intelligence technologies into educational processes requires improving academic support systems and cultivating digital skills. The study brings novel policy directions for higher education institutions and educational leaders as well as administrators.